Perioperative and Medium-Term Outcome of Bridge to Surgery for Obstructive Colorectal Cancer - Osawa, Hideki; Ikeshima, Ryo; Yoshioka, Shinichi; Uemura, Kohei; Okauchi, Yoshitaka; Maruyama, Minami; Ikeda, Yuji; Nomura, Tomonori; Marukawa, Daiki; Taniguchi, Yoshiki; Asukai, Kei; Masuzawa, Toru; et al. (Gan to kagaku ryoho, 2024)
Bridge to surgery(BTS), in which a self-expandable metallic stent(SEMS)is implanted for obstructive colorectal cancer and surgery is performed after decompression, is now widely practiced in Japan. We reviewed the outcomes of 31 patients with Stage Ⅱ or Ⅲ colorectal cancer who underwent radical resection after SEMS implantation at our hospital between January 2015 and December 2020. The mean age of the patients was 70.3 years; 17 were men and 14 were women. The median interval time from SEMS implantation to surgery was 23 days, and all patients underwent laparoscopic surgery. Four patients experienced complications of Clavien-Dindo Grade Ⅱ or higher. Fifteen patients had positive lymph nodes. Postoperative adjuvant chemotherapy was administered to 15 patients. The 3 years recurrence-free survival(RFS)rate was 69.3%, and the 3 years overall survival(OS)rate was 79.7%. These results suggest that BTS after SEMS implantation for obstructive colorectal cancer is safely performed at our hospital.